The Implementation Of Halal Food Labeling Based On The Technical Barriers To Trade (TBT) Agreement By Indonesia - Zoura Junita Khasahab; Wardah Wardah (Fakultas Hukum Universitas Syiah Kuala, 2018)
The World Trade Organization (WTO) is an international multilateral trade organization that sets rules between nations with members around the world. It has regulated The Technical Barrier to Trade (TBT) Agreement as source of law for its members in decided technical regulations, standards and conformity assesment procedures. Technical regulations and Standard deal with terminology, sysmbol, packaging, marking and labeling requirements. Meanwhile there is Halal, an arabic word means allowed and lawful, which products characteristic that provides information especially, Muslim as major consumers, that a product can be consumed and qualified if it put on halal label. Food labeling framework aims to regulate different interest and by providing halal label it gives information and fulfill consumer rights for certain consumers. The focus of the research is to overiew howlabel and standard based on TBT Agreement and How Indonesia implemented halal label due to Indonesia Law No. 33 of 2014 about Jaminan Produk Halal, some product enter Indonesia market shall obtain Indonesia halal standard and Indonesia halal certificate.This research is conducted under normative method. The data is accumulated from primary resources such as Law and Regulation, than secondary resources including legal text book, journal and paper, thus with tertiary resources such as dictionary.The TBT Agreement has no explicit defined the term of TBT, there is only definitions of the main elements, such as technical regulation, standard and conformity assessment procedures. The term of TBT refers to mandatory technical regulations and voluntary standards that define spesific characteristic a product should have. The WTO members given authorizing by the TBT to take such measures for consumer interest but based to some basic principles and does not violance TBT Agreement. Halal label on products especially food is information display of written that allowed Muslim to consume based on it is believe. In the WTO there are no special arrangement that regulate such halal matters, but the WTO recognizes the Codex Alimentarius and refers it as an international standard. Codex Alimentarius has been regulate general guidelines for uses of the term Halal since 1997. The TBT Agreement does not mention by name the standard-setting institution, the standards of which it recognized. However according to article 2.4 of TBT simply calls on countries to use international standard every time relevant international standard exist.Indonesia law No. 33 of 2014 about Jaminan Produk Halal begins transformation of halal label in Indonesia market. Which changed halal voluntary labeling into halal mandatory labeling, effected parties, herein Brazil which requesting consultation in 2014. Furthermore, with enacted law No. 33 of 2014 about Jaminan Produk Halal, it also changed the authority of related halal. Whereas before, the one and only one has authority for decided halal label until certifiated halal label handle by the MUI, but nowaday with law No. 33 of 2014 about Jaminan Produk Halal will separating the power by forming a new body that will regulate halal, reducing MUI task but not eliminating MUI participation in regulating halal.